The Influence of Individual Characteristics, Work Achievement, Ability, and Work Satisfaction on Employee Performance at Panai Hulu District Office Tanjung Sarang Elang - Jimmi Tasman; Mulya Rafika; Abd Halim (Daengku: Journal of Humanities and Social Sciences Innovation, 2023)
This study aims to analyze the effect of individual characteristics, work performance, ability and job satisfaction on employee performance at the Panai Hulu sub-district office, Tanjung Sarang Elang. The research method used in this research is quantitative. In this study, the population was 40 employees of the Panai Hulu Sub-district Office, Tanjung Sarang Elang. The research sample used a saturated sampling technique by attracting the entire existing population to be used as a research sample with a total of 40 people. Data collection techniques used were observation, documentation studies and questionnaires. The method of analysis of this research is multiple linear regression with the SPSS program. The results of the study prove that individual characteristics have a positive and significant effect on employee performance at the Panai Hulu Tanjung Sarang Elang sub-district office. Work performance has a positive and significant effect on employee performance at the Panai Hulu Tanjung Sarang Elang sub-district office. Capability has a positive and significant effect on employee performance at the Panai Hulu Sub-district Office, Tanjung Sarang Elang. Job satisfaction has a positive and significant effect on employee performance at the Panai Hulu Sub-district Office, Tanjung Sarang Elang. Individual Characteristics, Work Performance, Capabilities and Job Satisfaction simultaneously have a positive and significant effect on Employee Performance at the Panai Hulu Sub-district Office, Tanjung Sarang Elang. The coefficient of determination is 0.754, meaning that employee performance can be explained by the variables Individual Characteristics (X1), Work Performance (X2), Capability (X3) and Job Satisfaction (X4) of 75.4%, while the remaining 24.6% can be explained by variables others that were not examined in this study.